Flight Calls : Exploring Massachusetts through Birds - Nelson, John R. (Ornithologist) (Book collections on Project MUSE., 2019)
"The paths of different birds look like double helixes, flowing strands of hair, and migrating serpents, and they beckon with calls that have definite meanings. These mysterious creatures inspire growing numbers of birders in their passionate pursuit of new species, and writer John R. Nelson is no exception. In Flight Calls, he takes readers on explorations to watch, hear, and know Massachusetts's hummingbirds, hawks, and herons along the coasts and in the woodlands, meadows, and marshes of Cape Ann, Cape Cod, the Great Marsh, Mount Auburn Cemetery, the Quabbin wilderness, Mount Wachusett, and elsewhere. With style, humor, and a sense of wonder, Nelson blends his field adventures with a history of the birding community; natural and cultural history; bird stories from authors such as Henry David Thoreau, Emily Dickinson, and Mary Oliver; current scientific research; and observations about the fascinating habits of birds and their admirers. These essays are capped off with a plea for bird conservation, in Massachusetts and beyond"--